Strategi Bertahan Hidup Penambang Emas di Desa Bulontio Timur Kecamatan Sumalata Kabupaten Gorontalo Utara - Hatu, Dewinta Rizky R.; Latare, Sainudin; Lapasaw, Mohamad Riski (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This study aims to analyze the survival strategies implemented by gold miners in Bulontio Timur Village, Sumalata District, North Gorontalo Regency. The research method used is a qualitative approach with a descriptive design. Data were collected through observation techniques, in-depth interviews, and documentation studies. The results of the study indicate that gold miners in Bulontio Timur Village rely on mining as their main source of income because agricultural products are not sufficient for their living needs, especially during the dry season or crop failures. In carrying out mining activities, miners must ask permission from the mine owner known as the "boss", with a clear and transparent profit-sharing system. Social capital, such as good social relations between miners and mine owners, plays an important role in the continuity of their work. Trust and social networks allow miners to survive in conditions full of uncertainty. In addition, loans from mine owners are also one of the common survival strategies used by miners when mining results are insufficient for their needs. This loan is usually in the form of money or other mining needs that will be repaid after the miners obtain mining results. Overall, this study emphasizes the importance of income diversification, strengthening social capital, and managing economic uncertainty in the survival strategies of miners in Bulontio Timur Village. Keywords: Survival Strategy, Miners, East Bulontio Village